2022
DOI: 10.3389/fonc.2021.783339
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Liver Resection for Metabolic Dysfunction-Associated Fatty Liver Disease or Chronic Hepatitis B-Related HCC

Abstract: AimsThis study aims to determine differences in severity of background liver disease at hepatocellular carcinoma (HCC) diagnosis and long-term survival outcomes among patients undergoing liver resection for HCC in the background of metabolic dysfunction-associated fatty liver disease (MAFLD) compared to chronic hepatitis B (CHB) alone or concurrent CHB (CHB/MAFLD).MethodsPatient demographics and comorbidities, clinicopathologic data, perioperative and long-term outcomes among patients who underwent liver resec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…Eight studies reported the incidence of perioperative complications, which was higher in the observation group than in the control group in four studies 49 , 54 , 56 , 59 , lower in the observation group in two studies 19 , 57 , and similar between the observation and control groups in the other two studies 20 , 21 . Pooling the patients across all eight studies showed that the rate of major complications was similar between the observation group (8.98 per cent, 93/1035) and control group (9.0 per cent, 466/5153; P = 1.000).…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…Eight studies reported the incidence of perioperative complications, which was higher in the observation group than in the control group in four studies 49 , 54 , 56 , 59 , lower in the observation group in two studies 19 , 57 , and similar between the observation and control groups in the other two studies 20 , 21 . Pooling the patients across all eight studies showed that the rate of major complications was similar between the observation group (8.98 per cent, 93/1035) and control group (9.0 per cent, 466/5153; P = 1.000).…”
Section: Resultsmentioning
confidence: 95%
“…S1 ). Compared with patients with HCC of other aetiologies, those with NAFLD-related HCC had a higher BMI, they were older in 11 studies 19 , 21 , 49–52 , 54–57 , 59 , and they showed significantly lower cirrhosis rates in 11 studies 19–22 , 48 , 49 , 51 , 53–55 , 57 of the 15 that reported cirrhosis rates 19–22 , 48 , 49 , 51 , 53–60 . When cirrhosis rates were calculated across all patients pooled from the studies, prevalence was significantly lower in the observation group than in the control group ( P < 0.001).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“… 79 – 82 Several recent retrospective studies have compared outcomes after hepatic resection to treat NAFLD-related HCC or HCC of other etiologies. Some studies suggested that patients with NAFLD-related HCC had longer survival, 83 , 84 while others found similar overall survival among patients with HCC of different etiologies. 85 , 86 Two recently published meta-analyses concluded that patients with NAFLD-related HCC had better overall and disease-free survival after hepatic resection than patients with HCC of other etiologies.…”
Section: Hepatic Resection and Local Ablationmentioning
confidence: 99%